Proposed curriculum for physical education class and its impact on the development of some elements of physical fitness - Jawad, Adnan; Monir , Yasser; Saleh, Jassem (Journal of Physical Education, 2023)
The aim of research is :Preparation teaching program for sport education lesson to pro some laments fitness for first secondary first class , and to know how program influence develop some fitness elements for research sample.The researchers hypothesis there are statistical differences between pre. And post – test to the expense and controlling group in some fitness elements for the after post – test in addition to the differences results between after tests for exercise and controlling group in some fitness elements for controlling group.The experimental curriculum used the research sample include ( 50 ) secondary pupils , ( 25 ) pupils in each group.Conclusion :- There are influence for suggestion program in some fitness elements development.Recommendation :- The important of total development for all fitness elements.